Air–water properties of unsteady breaking bore part 2: Void fraction and bubble statistics. (February 2023) - Shi, Rui; Wüthrich, Davide; Chanson, Hubert
Abstract: Continuing from the part 1 (Shi et al., 2022) this paper presents an experimental investigation of transient void fraction and bubble statistics in a highly turbulent breaking bore with F r 1 = 2 . 4 . The measurements were conducted using a combination of dual-tip phase-detection probes and an ultra-high-speed video camera. The enclosed bubble detection technique (EBDT) used the synchronised probe and camera signals to provide the contour of instantaneous void fraction in the bore roller. The ensemble-averaged void fraction was derived, and compared to analytical solutions of air diffusion models. The bubble statistics were characterised by the bubble clustering properties, pseudo bubble count rate and bubble size spectrum. The clustering data showed the non-random bubble grouping in the shear layer, and the bubble size distributions N ( r ) followed a commonly adopted bubble break-up model: N ( r ) ∝ r − m, where r was the equivalent bubble radius in the present study. The comparison indicated that, in the breaking bore, its air diffusion process was similar to that in a stationary hydraulic jump, and the bubble break-up process was comparable to that in breaking waves. Graphical abstract: Highlights: A novel non-intrusive image-based technique, enclosed bubble detection technique (EBDT), was developed to provide a dense distribution of void fraction in a breaking bore roller. The EBDT described the air-diffusion process in the breaking roller, and the ensemble-averaged void fraction were compared well with the analytical solutions. From EBDT, the bubble size spectrum was obtained from a large dataset, showing a relationship of N ( r ) ∝ r − m, for m = 4 / 3 for r < 2 mm, where r is the equivalent radius.